Effects of clenbuterol on electro-acupuncture analgesia and morphine analgesia in rats - SU Shu-yi; ZHENG Shu-qi; LU Yun-yang (Acta Pharmacologica Sinica, 2016)
Rats were given electro-acupuncture (EA) at “Zusanli” and “Sanyinjiao” points bilaterally with increasing voltages (1-2-3V) for 30 min. The average of pain threshold in the period as determined by the tailflick test was taken as the index of the analgesic effect of EA. Clenbuterol 0.4 mg/kg ip had no significant effect on the basal pain threshold, but dereased the analgesic effect of EA. Afrer 35 min, the analgesic effect of EA was lowered by 85% (p＜0.001) as compared with the control rats. CL 0.5,0.75, and 1 μg were injected into the lateral cerebral ventricles. After 45 min, the analgesic effect of EA was lowered by 43%, 49% and 57% of the saline controls repectively (p＜0.01). CL (icv 2 or 4 μg) elevated the pain threshold markedly and the effect lasted more than 2 h (p＜0.02) as compared with morphine alone, indicating that CL enhanced the analgesic effect of morphine. It seemed that an activation of β2-receptors would decrease the analgesic effect of EA but increase that of morphine.